2018
DOI: 10.14202/vetworld.2018.172-176
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of small ruminant caprine arthritis encephalitis lentivirus among goats from selected small ruminant farms in Selangor, Malaysia

Abstract: Background and Aim:Caprine arthritis encephalitis (CAE) is an important viral disease of small ruminants particularly in dairy goats with severe social and economic implication. Hence, this study was designed to determine the seroprevalence of CAE virus (CAEV) among goat population in selected small ruminant farms in Selangor and the risk factors associated with the occurrence of the disease.Materials and Methods:Blood samples were collected from a total of 91 goats selected at random. Blood serum was harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 18 publications
5
23
4
Order By: Relevance
“…The overall seroprevalence of SRLVs infection in goats has been reported in several countries. Similar seroprevalence (2.9-38.5%) that the ones reported in Romania were found in India (3.3%) [ 24 ], Oman (5.1%) [ 25 ], Sudan (5.8%) [ 26 ], Belgium (6%) [ 27 ], Malaysia (8.9%) [ 28 ], Japan (10%) [ 29 ], Liban (13.1%) [ 30 ], Kosovo (15.6%) [ 31 ], Italy (18.6%) [ 32 ], and Algeria (29.7%) [ 33 ]. Lower seroprevalence was reported in Switzerland (0.06%) [ 34 ] and higher in Brazil (49.5%) [ 35 ], Poland (51.6%) [ 36 ], Croatia (53.7%) [ 37 ], and Taiwan (61.7%) [ 38 ].…”
Section: Discussionsupporting
confidence: 73%
“…The overall seroprevalence of SRLVs infection in goats has been reported in several countries. Similar seroprevalence (2.9-38.5%) that the ones reported in Romania were found in India (3.3%) [ 24 ], Oman (5.1%) [ 25 ], Sudan (5.8%) [ 26 ], Belgium (6%) [ 27 ], Malaysia (8.9%) [ 28 ], Japan (10%) [ 29 ], Liban (13.1%) [ 30 ], Kosovo (15.6%) [ 31 ], Italy (18.6%) [ 32 ], and Algeria (29.7%) [ 33 ]. Lower seroprevalence was reported in Switzerland (0.06%) [ 34 ] and higher in Brazil (49.5%) [ 35 ], Poland (51.6%) [ 36 ], Croatia (53.7%) [ 37 ], and Taiwan (61.7%) [ 38 ].…”
Section: Discussionsupporting
confidence: 73%
“…2014 ). This study has revealed 21.4% (95% CI: 15.8–28.6) apparent and 20.6% (95% CI: 14.5–27.8) seroprevalence of CAEV among small ruminants, which is higher than a preliminary study that reported a 8.42% seroconversion rate among goats from Selangor, Malaysia ( Jesse et al . 2018 ), but is comparable to a previous survey by Al-Qudah et al .…”
Section: Discussioncontrasting
confidence: 57%
“…The estimation of the sample size for herd level true prevalence of CAE in the study area was calculated using EpiTools ® statistical software according to Humphry et al . (2004) based on the assumptions of 95% confidence interval (CI), 5% desired absolute precision, 100% specificity, 99% sensitivity, and 8.42% assumed true prevalence as reported by Jesse et al . (2018) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hobbyist farms in most cases are multispecies farms, and small ruminant lentivirus control programs should be concentrated on both sheep and goats. The lack of regular screening for small ruminant lentiviruses is increasing the spread of the disease [45][46][47].…”
Section: Discussionmentioning
confidence: 99%